カキ ナンキョク タイリュウケン チュウ ノ エアロゾル リュウシ ノ ブンプ ト コンゴウ ジョウタイ ANTSYO-II(AGAMES) カンソク - 原, 圭一郎; ハラ, ケイイチロウ; 平沢, 尚彦; ヒラサワ, ナオヒコ; 山内, 恭; ヤマノウチ, タカシ; 和田, 誠; ワダ, マコト; Herber, Andreas; Hara, Keiichiro; Hirasawa, Naohiko; Yamanouchi, Takashi; et al. (2010)
P(論文) 2006年12月～ 2007年1月に,南極域で航空機を使用した大気観測(ANTSYO-II: AGAMES)を実施した.エアロゾル観測及びエアロゾルの直接採集は,Neumayer基地,Kohnen基地,S17航空拠点(昭和基地付近)で実施した.個別粒子分析用のエアロゾル試料は1段式のインパクターを用いて,地上付近から約7500 mの高度領域で捕集し,28回の観測飛行で試料を得た.個別粒子分析の結果,主要なエアロゾル粒子は硫酸粒子だった.さらに,南極域上空でも燃焼起源のエアロゾル粒子(スス・K含有硫酸塩)が確認された.また,土壌粒子や海塩粒子も自由対流圏中で観測された.この結果は,夏季南極において燃焼起源粒子や土壌粒子が,対流圏上部経由で低・中緯度域から南極域へ輸送されていることを示唆している.エアロゾル数濃度の空間分布では,海洋表面からの海塩粒子発生によるエアロゾルの水平方向の濃度勾配が確認された. Airplane-borne atmospheric measurements (ANTSYO-II: AGAMES) were carried out in the Antarctic regions in December 2006-January 2007. Aerosol measurements and direct aerosol sampling were done around Neumayer, Kohnen, and S17 (close to Syowa Station). Aerosol samples for individual particle analysis were obtained from 28 scientific flights from near ground to 24000 ft (ca. 7500 m) during the campaign using a one-stage aerosol impactor. Preliminary results of individual particle analysis indicate that sulfate particles (mostly H_2SO_4) were dominant aerosol constituents in all flights. In addition, combustion-origin aerosol particles (e.g., soot and sulfate containing K) were identified even in the upper troposphere in Antarctic regions. Also, mineral-like and sea-salt-like particles were identified in the free troposphere. This strongly suggests that combustion-origin aerosol particles and mineral particles were transported from low- and mid-latitudes toward Antarctic regions via the upper free troposphere in the austral summer. Spatial distributions of the number concentrations of aerosol particles indicate horizontal gradient of aerosols from the continent to the open water area due to emission of sea-salt particles from the sea surface. departmental bulletin paper